HOLOCENE DUNE ACTIVITY AND ENVIRONMENTAL CHANGE IN THE PRAIRIE PARKI AND AND BOREAL FOREST, CENTRAL SASKATCHEWAN, CANADA - Wolfe S.A.; Ollerhead J.; Huntley D.J.; Lian O.B. (My University, 2006)
Past aeolian activity was reconstructed at four dunefields in the prairie parkland and boreal forest of central Saskatchewan to elucidate landscape response to environmental change. Optical ages from stabilized dunes in the boreal transition ecoregion indicate two episodes of activity. The first, at about 11 ka, corresponds to a period of early-Holocene parkland and grassland cover following deglaciation and drainage after about 13.0 ka, and brief establishment of boreal forest. The second, between about 7.5 and 5 ka, corresponds to a period of mid-Holocene parkland-grassland cover. Optical ages from dunefields in the prairie parkland primarily record mid-Holocene activity, between about 7.5 and 4.7 ka, corresponding to a period of grassland cover, with some reworking continuing into the late Holocene. Although this area was deglaciated by about 13.5 ka, there is no evidence of early-Holocene dune activity, suggesting that mid-Holocene activity may have reworked earlier deposits here. Consequently, much of the morphology and stratigraphy observed in these dunefields are associated with mid-Holocene activity, likely associated with increased aridity and reduced vegetation cover at that time. This study provides the most northerly evidence of mid-Holocene dune reactivation on the Great Plains, lending support to the assertion that aeolian activity was widespread at that time.
Keywords: SAND DUNES; NORTHERN GREAT PLAINS; PRAIRIE PARKLAND; BOREAL FOREST; MID-HOLOCENE; PALAEOENVIRONMENTS; OPTICAL DATING; CANADA; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен